(untitled) (Texas Journal of Agriculture and Biological Sciences, 2022)
In the conditions of the Surkhandarya region, the use of growth stimulants Humimax to obtain an early and high-yielding re-crop of sunflower. With the use of growth stimulants Humimax (seeding rate 0.75 l/t; spraying of plants in phase 3-4 leaves 0.4 l/ha) had a positive effect on all seed, growth, development and productive seed